Farmers’ Perception Regarding Dissemination of Improved Agricultural Technology through FFS in Tehsil Rawalpindi - Iqbal, Mobushir; Imam, Muhammad Fakhar; Rana, Hafiz Amjad Ali; Khan, Nasir Abbas; Qayyum, Muhammad Fakhar; Haider, Samsam (PSM Biological Research, 2017)
The agricultural sector is one of the major sectors of Pakistan’s economy having lion share in the GDP. Hither to, there are many approaches applied in the country for smooth running of the extension services but unfortunately, none has changed the desired objectives. To disseminate the agricultural knowledge more efficiently and effectively extension workers have been using a variety of approaches. FFS is one of the agricultural extension approach introduced in some districts of Punjab province in 2005-06. Both public and private sectors have been investing a lot on the development of FFS. This current study was conducted to assess the role of FFS in transfer of upgraded agricultural technology among the farmers in Tehsil Rawalpindi. Simple random sampling was used according to the nature of the topic and objectives. A sample of 120 farmers, who were in collaboration with farmer field school, was taken to collect the data. The results showed that most of the farmers (38.33%) of the respondents joined FFS. An overwhelming majority (84.33-95.00%) of the respondents agreed about FFS trainings to be conducted on the suitable time and place. The FFS provide a chance for learning-by-doing, based on principles of non-formal education.